Mozambique’s agrifood system structure and drivers of transformation - Benfica, Rui; Diao, Xinshen; Pauw, Karl; Thurlow, James; Ellis, Mia (International Food Policy Research Institute, 2023)
Mozambique was one of the fastest-growing countries in sub-Saharan Africa between 2009 and 2014, with annual growth averaging about 7 percent (INE 2020; World Bank 2023a). However, adverse economic circumstances resulted in a significant weakening of economic growth, which averaged only 4.6 percent over the period 2014 to 2019 (INE 2020; World Bank 2023a). Restrictive COVID-19 policymeasures introduced in 2020 further stifled the economy, resulting in negative growth in 2020 and low growth in 2021. Like many other countries, Mozambique was adversely affected by global commodity market disruptions resulting from the onset of Russia-Ukraine war in 2022 and the global recession in 2023 (Arndt et al. 2023; Diao and Thurlow 2023). Mozambique’s growth is expected to recover in the coming years, with projections of 5.0 percent growth in 2023 and 8.0 percent in 2024 (World Bank 2023b), suggesting the economy is inching back toward its pre-pandemic growth trajectory.